Periodontal treatment needs and workforce requirements: Comparisons between the normative and sociodental approaches using different skill mix models - Ab-Murat, N.; Sheiham, A.; Tsakos, G.; Watt, R. (Blackwell Publishing, 2015)

(untitled)
Objectives:Assessment of dental treatment needs has predominantly been based on the normative approach, despite its numerous limitations. The sociodental approach is a more rational method of needs assessment as it incorporates broader concepts of health and needs and behavioural propensity. This study compares estimates of periodontal dental treatment needs and workforce requirements for different skill mixes using normative and sociodental approaches among a sample of adults in Malaysia. Methods: A cross-sectional study was carried out on 732 Malaysian adults aged 30-54years. Subjects' normative and sociodental needs for periodontal treatment were assessed using WHO criteria, an oral health-related quality of life measure (the Oral Impacts on Daily Performances index), and behavioural propensity measures for toothbrushing and smoking behaviour. The proportion of subjects requiring periodontal treatment and the numbers of dentists and dental therapists required to treat them using the normative and sociodental approach were compared using different skill mix models. Results:The estimates of need for periodontal treatment using the sociodental approach were 90% lower than the respective estimates using the normative need method. Overall, 14.43 dentists would be required per 100000 people using the normative approach compared to 2.32 for the sociodental approach. When skill mix models were used, the number of dentists required decreased by almost 70% when more periodontal procedures were delegated to dental therapists. Conclusions:Using the sociodental approach resulted in much lower estimates of dental need and workforce requirements for periodontal treatment than using the normative method. Using dental therapists markedly reduced the numbers of dentists needed for periodontal treatment.